WAYS TO CREATE A HEALTHY LIFESTYLE IN THE FAMILY (Web of Teachers: Inderscience Research, 2025)
This article explores effective strategies for fostering a healthy lifestyle within the family setting. It emphasizes the importance of balanced nutrition, regular physical activity, mental well-being, and positive communication habits. The study highlights how consistent routines, mutual support, and shared goals contribute to long-term health benefits for all family members. Special attention is given to the role of parents as role models and the influence of home environments on children's habits and development.